Quantum Mechanical Calculations for Some PINH Cs Symmetry Schiff Bases as Corrosion Inhibitors for Mild Steel - Majed Kubba, Rehab; Kareem Abood, Fatin (Iraqi Journal of Science, 2023)
Density Functional Theory (DFT) at the B3LYP/6-311G basis set level was performed on six new substituted Schiff base derivatives of PINH [(phenylallylidene) isonicotinohydrazide], The calculated quantum chemical parameters correlated to the inhibition efficiency are EHOMO (highest occupied molecular orbital energy), ELUMO (lowest unoccupied molecular orbital energy), the energy gap [ΔE(HOMO-LUMO)], hardness (η), softness (S), dipole moment (μ), electron affinity (EA), ionization potential (IE), the absolute electronegativity (χ), Global electrophilicity index ( ) and the fraction of electron transferred (ΔN), all have discussed at their equilibrium geometry and their correct symmetry (Cs). Comparisons of the order of inhibition efficiency of the Schiff bases derivatives, and local reactivity were analyzed using Mulliken population analysis. The local reactivity has been studied through condensed softness indices in order to predict both the reactive centers and to know the possible sites of nucleophilic and electrophilic attacks. Also vibration frequencies and IR absorption intensities were carried out for the calculated Schiff bases molecules. Also some physical values were studied such as heat of formation and total energy.